2021
DOI: 10.1021/acs.analchem.0c04518
|View full text |Cite
|
Sign up to set email alerts
|

More Symmetrical “Hot Spots” Ensure Stronger Plasmon-Enhanced Fluorescence: From Au Nanorods to Nanostars

Abstract: Plasmon-enhanced fluorescence (PEF) is considered to be a powerful signal amplification technology to overcome intrinsic shortcomings of photobleaching and brightness of the traditional fluorescent dyes. Nevertheless, exploitation of PEFbased probes for bioimaging application is still at a very early stage. In this work, a simple but powerful gold nanostar (Au NST)@ SiO 2 -based PEF probe with 20 symmetric "hot spots" was developed for highly sensitive "lighting up" in situ imaging of intracellular microRNAs (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 47 publications
1
47
0
Order By: Relevance
“…The proposed biosensor was compared with the reported methods for miRNA-21 detection, and it was found that this strategy had higher sensitivity and possessed a lower detection limit (Table S2). …”
Section: Resultsmentioning
confidence: 99%
“…The proposed biosensor was compared with the reported methods for miRNA-21 detection, and it was found that this strategy had higher sensitivity and possessed a lower detection limit (Table S2). …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the capability of the NIR light-activatable UTDS to dynamically monitor the fluctuation of intracellular miRNA contents was evaluated. Here, miRNA-21 mimics were used to upregulate and an miRNA-21 inhibitor was used to downregulate miRNA-21 expression levels in HeLa cells, according to a previous work . Compared with untreated HeLa cells, mimic-treated HeLa cells showed obviously enhanced green fluorescence, while inhibitor-treated HeLa cells showed obviously decreased green fluorescence (Figure S13), confirming that the fluctuation of intracellular miRNA contents can be dynamically monitored using UTDS, which is of high significance for disease diagnosis and evaluation of therapeutic effect.…”
Section: Resultsmentioning
confidence: 99%
“…The localization of fluorophores near metal nanoparticle will lead to dramatic fluorescent signal enhancement on the nanometer scale and allows for an even lower LOD for early disease detection and clinical diagnosis applications. Gao et al constructed a versatile AuNSs@SiO 2 -based plasmon-enhanced fluorescence probe together with 20 symmetric “hot spots” for in situ “lighting up” imaging of intracellular miRNAs [ 55 ]. By regulating the thickness of the silica shell, the distance between AuNSs and fluorescent dyes was controlled, and an optimum fluorescence enhancement (21-fold) was obtained when the silica shell was of approximately 22 nm thickness.…”
Section: Plasmonic Gold Nanostructures For Biosensing In Vitromentioning
confidence: 99%
“…Reprinted with permission from ref. [ 55 ], Copyright 2021 American Chemical Society. B Schematic representation of the nanogap antennas assembly for target miRNA detection.…”
Section: Plasmonic Gold Nanostructures For Biosensing In Vitromentioning
confidence: 99%